Effect of Xylocarpus granatum Bark Extract on Amelioration of Hyperglycaemia and Oxidative Stress Associated Complications in STZ-Induced Diabetic Mice. (2nd May 2019) - Das, Swagat Kumar; Prusty, Arpita; Samantaray, Dibyajyoti; Hasan, Mojeer; Jena, Srikanta; Patra, Jayanta Kumar; Samanta, Luna; Thatoi, Hrudayanath
Abstract : Xylocarpus granatum is a medicinal mangrove plant, traditionally used for the treatment of diarrhoea, cholera, fever, dyslipidaemia, inflammation, etc. The present study was aimed to evaluate the in vitro antidiabetic ( α -glucosidase inhibition assay) and antioxidant (ABTS scavenging and metal chelating assay) activities of ethanol, methanol, and aqueous extracts of leaves and barks of X. granatum followed by in vivo antidiabetic and antioxidant evaluation of ethanol bark extracts in streptozotocin- (STZ-) induced diabetic mice. The in vitro evaluation revealed higher α -amylase inhibition and ABTS scavenging activities in ethanol bark extracts of X. granatum (XGEB). Administration of XGEB at 100 and 200 mg/kg BW doses to STZ-induced diabetic mice resulted in significant decrease (P < 0.05) in blood glucose, triglyceride (TG), total cholesterol (TC), serum glutamate oxaloacetate transaminase (SGOT), serum glutamate pyruvate transminase (SGPT), and urea levels in the serum of the extract administered groups as compared to diabetic control group. The levels of SOD, CAT, GPx, GR, and GST in liver along with LPx, SOD, GST, and GR activities in brain tissues were found to be ameliorated in XGEB treated diabetic mice. Histopathological alternations of liver tissues were also found to be restored in XGEB treated diabetic groups. The HPLC fingerprint analysis of XGEB revealed the presence of simple polyphenols, isoflavone, and flavonol-like compounds. The DSC and UV-VIS analysis also confirmed the presence of phenolic compounds in XGEB. The GC-MS analysis of XGEB showed the presence of a number of bioactive compounds. These results demonstrated the beneficial effect of XGEB in controlling hyperglycaemia and ameliorating oxidative stress associated complications associated with diabetes.